Catalytic transesterification of waste cooking oil using Fe-modified chicken bone catalyst: characterization and optimization - Nurul Izzati Saharuddin; Muhammad Afiq Danial Mohamed Nassir; Aina Zulaikha Muzafar Shah; Tengku Shafazila Tengku Saharuddin; Nurul Jannah Abd Rahman; Syahirah Yahya; Farah Wahida Harun (Penerbit Universiti Kebangsaan Malaysia, 2025)
Food waste, including non-reusable materials like chicken bones, forms a significant portion of solid waste. In Malaysia, approximately 540,000 tons of waste cooking oil (WCO) is discarded annually without proper treatment. Chicken bones, rich in calcium, can be utilized as a heterogeneous catalyst in biodiesel production, addressing waste management issues. However, the use of chicken bone as a catalyst presents challenges such as the unmodified chicken bones often require a pre-treatment step to reduce high free fatty acid (FFA) content in WCO to prevent saponification, limiting their efficiency. Hence, this research endeavors to innovate by converting WCO into biodiesel via a transesterification reaction, leveraging waste chicken bones as a catalyst. The calcined waste chicken bone (CB) was modified to form 5 wt% Fe-CB, and 10 wt% Fe-CB. The catalysts were found to have similar physical characteristics in terms of the structure and surface morphology observed from XRD, N2 adsorption-desorption, and SEM analysis. Among the catalysts, 10 wt% Fe-CB, produced the highest yield of fatty acid methyl esters (FAME), reaching 72.52%, under mild reaction conditions (10:1 methanol-to-WCO molar ratio, 1 wt% catalyst loading, 60 oC reaction temperature and 4 h reaction time). The capability of 10 wt% Fe-CB to produce a higher fatty acid methyl esters (FAME) yield than 5 wt% Fe-CB and calcined CB was due to the presence of CaO with binary transition metal oxides providing both acidic and basic sites, allowing for more efficient WCO conversion.